Fiscal states in sub-Saharan Africa: Conceptualization and empirical trends - Ane Karoline Bak; Matilde Jeppesen; Anne Mette Kjær (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper contributes to the debate on domestic revenue mobilization and statebuilding in the Global South by asking whether there are fiscal states in sub-Saharan Africa. To answer this question, we review the diverse understandings of the fiscal state across relevant literatures and explore which preconditions are necessary for the emergence of fiscal states. We define the fiscal state by a balanced relationship between taxation and borrowing as dominant revenue sources, and we distinguish it conceptually from the tax, debt, and rentier states. We analyse and show that the average sub-Saharan African country cannot be categorized as a fiscal state, and that this is to a large extent explained by the absence of economic preconditions. This finding is important because when African states are regarded as fiscal states, assumptions are made about their economic structures; yet, to the extent that these are absent, fiscal policy reforms are unlikely to carry long-term positive effects.
Keywords: H20; N17; O2; Y10; 330; fiscal states; sub-Saharan Africa; taxation; borrowing; debt state; rentier state